APLIKASI PUJIAN PENYEMBAHAN DALAM MENGATASI MASALAH KECEMASAN DI MASA LANJUT USIA DI IBADAH USIA EMAS (UMAS) GEREJA BETHEL INDONESIA TABGHA BATAM CENTER - Purba, Gomgom; Siahaan, Melinda; Suriyanti, Intan (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2024)
ABSTRACT The purpose of this research is to determine the application of praise and worship in overcoming the problem of anxiety in old age at the golden age service (umas) of the Bethel Indonesia Tabgha Church, Batam Center. Various problems arise in old age, one of which is anxiety. The problem of anxiety in the elderly is a serious problem that must be considered because it can increase the risk of disease and lead to death. Worship praise is the right solution in dealing with the problem of